Contribution of macroprudensial policy of central bank on microprudensial Islamic banking - Riduwan Riduwan; Rofiul Wahyudi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
The purpose of this research will be to answer the contribution of the macroprudential policy of Central Bank to the microprudential of islamic banking during the period of January 2008 - February 2016. The method used by quantitative analysis with panel data regression to be able to describe macroprudential policy contribution to FDR of islamic banking in Indonesia. Macroprudential policy instruments use Loan-to-Value Ratio (LTR), Statutory Reserves (GWM) based on Loan-to-Funding Ratio (LFR) and Countercyclical Capital Buffer (CCB). The islamic bankingmicroprudential instrument used is Financing to Deposit Ratio (FDR). The result shows that macroprudential policy contribution through LTV instrument to FDR has negative and significant influence. Statutory Reserves based on LFR on FDR have a positive and significant influence and CCB on FDR of Indonesia’s islamic banking shows negative and significant influence.